2023
DOI: 10.3904/kjim.2022.340
|View full text |Cite
|
Sign up to set email alerts
|

Association between eupatilin and reduction in small bowel bleeding in aspirin users and aspirin plus acid suppressant users

Abstract: Background/Aims: Capsule endoscopy (CE) has shown that low-dose aspirin occasionally causes small bowel (SB) bleeding. We herein evaluated the protective effects of mucoprotective agents (MPAs) on SB bleeding in aspirin users using the nationwide database of claims data from the National Health Insurance Service (NHIS).Methods: As CE is an insured procedure, we constructed an aspirin-SB cohort using NHIS claims data, with a maximum follow- up period of 24 months. Patients with anemia, melena, or hematochezia t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…DA-9601 demonstrated a protective effect against NSAIDs-induced gastroduodenal injury that was not inferior to that of misoprostol in previous double-blinded randomized clinical trials [16,17] with a significant reduction in small bowel bleeding in patients taking aspirin in a previous study using the Korean claim database. [18] However, unlike our study, which focused on patients with RA, these previous studies did not exclusively analyze individuals with arthritis. Previous studies have suggested that arthritis such as RA or osteoarthritis (OA) may render the GI tract more susceptible to damage by NSAIDs; [19–21] therefore, our data provide more pertinent information for preventive measures against serious GI complications in patients with arthritis receiving long-term NSAIDs.…”
Section: Discussionmentioning
confidence: 96%
“…DA-9601 demonstrated a protective effect against NSAIDs-induced gastroduodenal injury that was not inferior to that of misoprostol in previous double-blinded randomized clinical trials [16,17] with a significant reduction in small bowel bleeding in patients taking aspirin in a previous study using the Korean claim database. [18] However, unlike our study, which focused on patients with RA, these previous studies did not exclusively analyze individuals with arthritis. Previous studies have suggested that arthritis such as RA or osteoarthritis (OA) may render the GI tract more susceptible to damage by NSAIDs; [19–21] therefore, our data provide more pertinent information for preventive measures against serious GI complications in patients with arthritis receiving long-term NSAIDs.…”
Section: Discussionmentioning
confidence: 96%
“…Although the study was limited by a small cohort, the number of diagnoses of NSAID enteropathy had increased, and this increase could be attributed to the aging population [ 30 ]. Our study group, using the nationwide database of claims data from the NHIS, found that MPAs had a protective effect against small bowel bleeding in patients using aspirin [ 31 ]. In that study, patients with anemia, melena, or hematochezia that occurred within 4 weeks before and after CE were suspected to have small bowel bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Small bowel bleeding occurred more frequently in patients who used acid suppressants concurrently with PPIs than in those who did not use acid suppressants concurrently with PPIs (1.3 vs. 0.5%). Subgroup analysis revealed that eupatilin significantly reduced the risk of small bowel bleeding in patients using aspirin concurrently with acid suppressants (HR, 0.23 vs. 2.55) [ 31 ]. However, the numbers of patients taking aspirin and those with small bowel bleeding were relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…In this nationwide cohort study, we used data from the KNHIS database 6 . The KNHIS database is considered to represent the entire South Korean population, and the details of this database have been previously described 7,8 . All insured Korean people undergo annual or biennial health examinations that are supported by the KNHIS.…”
Section: Data Sourcesmentioning
confidence: 99%